Compact broadband printed quasi‐Yagi antenna with series‐fed double monopole. Issue 4 (8th January 2020) - Chaudhari, Amar D.; Ray, K. P.
Abstract: In this study, a new configuration of a low profile, broadband printed quasi‐Yagi antenna with two directly fed monopoles has been proposed. The property of a printed monopole antenna with a simple microstrip feed‐line has been used to simplify feeding structure of the printed quasi‐Yagi antenna. A broad bandwidth is achieved by cascading another monopole element of different lengths in a series to obtain two nearby resonances. The proposed antenna consists of two driven monopoles on one side of the dielectric substrate, whereas, on the other side, a reflector and a director are realized as parasitic monopole elements, directly on the ground plane. The measured impedance bandwidth of 70.2% (1.46‐3.05 GHz) with stable gain ranging from 4.7 to 5.3 dBi in the entire bandwidth has been achieved. The antenna has the front‐to‐back ratio better than 10 dB and cross‐polarization level below −20 dB in the direction of maximum radiation over the entire bandwidth. The simulated performance of the antenna has been experimentally verified with good agreement.